Cambodia Power Sector : Technical Assistance for Capacity Building of the Electricity Authority of Cambodia - World Bank (Washington, DC, 2014)
The Electricity Authority of Cambodia (EAC) is in its nascent stage of development. However, it has undertaken initial steps toward increasing public awareness of electricity regulation and issuing licenses to larger scale generators and distributors in urban areas. EAC's next important task is to formalize the operations of small-scale private operators in the rural areas. The regulatory framework for rural electricity operations in the country has yet to be fully developed. Guidelines and procedures are currently being drafted by EAC, but they still have to be tested thus, gradual revisions can be anticipated and precedents must be established. In addition, the scope of EAC's operations must be expanded to include, among other things, definitions of technical standards and procedures for determining tariff levels. In view of EAC's extensive work plan, the Energy Sector Management Assistance Program (ESMAP) has provided a grant toward the financing for a technical advisor to support EAC in these activities.